Monocyte esterase deficiency in malignant neoplasia. Issue 4 (April 1990) - Markey, G M; McCormick, J A; Morris, T C; Alexander, H D; Nolan, L; Morgan, L M; Reynolds, M E; Edgar, S; Bell, A L; McCaigue, M D
Abstract : A survey of the incidence of monocyte esterase deficiency in 4000 inpatients (including 808 with malignant neoplastic disease) and 474 normal controls was performed using an automated esterase method. A highly significant excess of patients with malignant disease and the deficiency was evident when compared with normal controls or all other patients. Within the group of patients with malignant disease the demonstrable excess occurred in B chronic lymphocytic leukaemia, non-Hodgkin's and Hodgkin's lymphoma, and carcinoma of the gastrointestinal tract. There was also a significant excess of patients with the deficiency attending the renal unit, both among patients who had had renal transplants and those who had not. A familial incidence of monocyte esterase deficiency was found in 19 (35%) of first degree relatives of those patients in whom family studies were done. It is suggested that the reason for the increased prevalence of the anomaly in these disorders might be that the diminution of esterase activity has a role in their development.